2015
DOI: 10.1128/jcm.01733-15
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variability of Serial Human Isolates of Salmonella enterica Serovar Typhimurium Associated with Prolonged Carriage

Abstract: c Salmonella enterica serovar Typhimurium is an important foodborne human pathogen that often causes self-limiting but severe gastroenteritis. Prolonged excretion of S. Typhimurium after the infection can lead to secondary transmissions. However, little is known about within-host genomic variation in bacteria associated with asymptomatic shedding. Genomes of 35 longitudinal isolates of S. Typhimurium recovered from 11 patients (children and adults) with culture-confirmed gastroenteritis were sequenced. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 31 publications
2
20
1
Order By: Relevance
“…Although this is a relatively low SNP rate, we were able to demonstrate that in independent cases, SNPs were found to be nonsynonymous substitutions or nonsense mutations in global virulence regulatory genes, including dksA, rpoS, hilD, melR, rfc, and barA, which may infer a pleotropic change in the transcriptional landscape of persistent Salmonella infection (154). Similarly, a nonsense mutation in another global regulator, flhC, encoding a master regulator of flagellum biogenesis, was reported by Octavia and colleagues for a 55-day S. Typhimurium persistence case (264). Moreover, we demonstrated that recrudescent isolates may harbor different compositions of plasmids and bacteriophages, suggesting loss and/or horizontal acquisition of mobile genetic elements during prolonged infection within the human host (154).…”
Section: Genetic and Phenotypic Changes Acquired During Salmonella Pementioning
confidence: 67%
See 1 more Smart Citation
“…Although this is a relatively low SNP rate, we were able to demonstrate that in independent cases, SNPs were found to be nonsynonymous substitutions or nonsense mutations in global virulence regulatory genes, including dksA, rpoS, hilD, melR, rfc, and barA, which may infer a pleotropic change in the transcriptional landscape of persistent Salmonella infection (154). Similarly, a nonsense mutation in another global regulator, flhC, encoding a master regulator of flagellum biogenesis, was reported by Octavia and colleagues for a 55-day S. Typhimurium persistence case (264). Moreover, we demonstrated that recrudescent isolates may harbor different compositions of plasmids and bacteriophages, suggesting loss and/or horizontal acquisition of mobile genetic elements during prolonged infection within the human host (154).…”
Section: Genetic and Phenotypic Changes Acquired During Salmonella Pementioning
confidence: 67%
“…A similar SNP substitution rate was found in patients who were persistently infected with invasive S. Typhimurium pv. ST313 in sub-Saharan Africa (263) or in S. Typhimurium associated with short-and long-term carriage, which showed an estimated mutation rate of 1.49 ϫ 10 Ϫ6 substitutions per site per year (264). Although this is a relatively low SNP rate, we were able to demonstrate that in independent cases, SNPs were found to be nonsynonymous substitutions or nonsense mutations in global virulence regulatory genes, including dksA, rpoS, hilD, melR, rfc, and barA, which may infer a pleotropic change in the transcriptional landscape of persistent Salmonella infection (154).…”
Section: Genetic and Phenotypic Changes Acquired During Salmonella Pementioning
confidence: 99%
“…After the disappearance of symptoms, Salmonella may still reside in the intestines of an adult for 4 weeks, and in children for up to 7 weeks. A small number of people demonstrates an asymptomatic carrier state of pathogenic bacteria for a year after the disappearance of symptoms [ 111 ]. In the majority of cases, nontyphoid salmonellosis does not require hospitalisation, and only fluid therapy is necessary in the cases associated with severe diarrhea.…”
Section: Salmonellosismentioning
confidence: 99%
“…Typhimurium isolates with no apparent adaptive values. For example, Octavia et al (2015b) analyzed the genomic variation of serial S . Typhimurium isolates in human infection related with prolonged carriage and found that the majority of SNPs observed were located in coding regions, most of which were nsSNPs in the genes involved with metabolism.…”
Section: Resultsmentioning
confidence: 99%